The Impact of Financial Integration on Institutions in Autocracies - Ramin Dadasov; Philipp Harms; Jens Oliver Lorz (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
It is often argued that a saticfactory institutional quality is prerequi- site for successfull financial integration. This paper analyzes the influence of financial integration on institutional quality. We construct a dynamic politico-economic model in which the ruling elite uses its political power to expropriate the entrepreneurial class. Although financial integration reduces capital costs for the entrepreneurs and therefore increases their gross profits, the elite counteracts this effect by raising the level of expropriation. Consequently, the net income of entrepreneurs may rise or decline depending on the respective magnitude of the countervailing effects. Since political power is linked to economic resources, financial integration also has consequences for the concentration of power in the hands of the elite and for the rise of the entrepreneurial class.
Keywords: F21; O16; P48; 330; Institutions; Capital Mobility; Political Economy